Industrialisation of Civil Engineering - Shirke, B. G. (Journal of Engineering Education Transformations, 1995)
"What is total industrialisation of civil engineering and establishment of building centres -nirmiti kendras - at least one at each tehsil all over the country, which can become the modern temples of allround development of rural areas".